Peculiarities of Production Cost Management in Ukrainian Companies in the Context of Economic Crisis - N. Y. Radionova (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
A vital condition for company’s survival in the market environment is rational management of production costs. The purpose of the study is to analyze various approaches to production costs management in Ukrainian companies in the conditions of economic crisis. Factors that affect business operation of domestic enterprises in times of economic crisis are outlined. The mechanism for production costs management at company level is shown; most common defects and mistakes in cost management systems are highlighted. The strategy for effective analysis of company costs is proposed, which covers the following phases: describe business processes existing in a company; build the model of actual business processes, analyze and improve it; optimize the work of personnel; improve the contacts with clients and suppliers (a vital step in the crisis conditions). It is argued that whenever a system for cost optimization is built, the right approach to austerity measures will be required, because a mistake in this matter can aggravate the company performance. Company managers responsible for measures on cost reduction need to take strategically right decisions that won’t trigger new problems for a company: the grown production risks (resulting from withdrawal from modernization of fixed assets), the reduced turnover (resulting from use of cheaper inputs), the reduced labor output (due to the decreased motivation, excessive downsizing of personnel or pay cuts).